Chilean Foreign Policy in Democracy, towards Global Integration - Salgado Ávila, Juan José; Quintremán Lara, Patricio (Latin American Journal of Trade Policy, 2018)
This article analyzes the government programs of presidential candidates, who then became presidents of Chile (1990-2016); its objective is to find and explain the continuities and discontinuities reflected in the Foreign Policy sections. To analyze the most important topics, the Comparative Manifestos Project (CMP) methodology is used, which, by analyzing content, categorizes in 56 areas, the phrases or quasi-sentences of the candidates in the political programs or manifestos during the pre-election period. First, the importance of the Foreign Policy is identified in each program. Then, the results obtained in the CMP are described, identifying the priority topics. Finally, the results are explained within the national and international context to obtain the motivations that each of the candidates had to incorporate these topics in the highest position of their Foreign Policy agendas.